Vocational Value Profiles of Students with Preferential Vocational Interest in Sport and Their Relationship with Personal and Academic Wellbeing - Evelia Franco (MDPI AG, 2021)
In recent years there has been a significant increase in the number of students who choose to pursue university studies related to the field of sports. However, there are no studies that have investigated the existence of differentiated profiles within students whose preferred vocational area is sport. The main objective of this study was to establish the profiles of students in the second year of Spain Bachillerato whose preferred vocational interest is sport, according to the two representative vocational values: (a) “to have a fun professional activity”; and (b) “to have a professional activity whose schedule makes it possible to reconcile personal and professional life”. In addition, the resulting groups were compared according to their perception of general and academic wellbeing and their identification with the other vocational values. Two hundred and thirty participants (MAge = 17.47; DTAge = 0.669; N = 171; 74.3% male and N = 59; 25.7% female) completed some validated measures. Three clusters emerged which did not differ in terms of general and academic wellbeing. Differences were found though in terms of some vocational values such “to help people”, “to develop one’s entrepreneurial initiative” or “to be self-employed”. The findings invite us to rethink the differences in the specific profiles of vocational values and their impact on employability opportunities, and to consider these approaches in the orientation of students who have among their priority options to study sport sciences.